Building composite indicators from a multicriteria approach: An empirical application for the performance appraisal and efficiency of the Spanish - El-Gibari-Ben-Said, Samira (UMA Editorial, 2021)
The increasing awareness around the world of the role that universities play in today's competitive environment highlights the need to assess them by using methods that are able to manage their diversity, complexity and multidimensional nature. On this premise, this doctoral thesis aims to go beyond simply providing a ranking of the Spanish public university system. To this end, this doctoral thesis is presented as a compendium of three research papers. Besides, some additional research questions related to these articles are presented. Specifically, recognizing the specific nature and complexity of a university system, this doctoral thesis has attempted to analyze the performance and efficiency of the Spanish public universities from a multicriteria approach. First, in order to evaluate the performance of a university system, a novel approach, based on the multicriteria reference point scheme, is proposed. This generalization, called Multiple Reference Point based Weak and Strong Composite Indicators (MRP-WSCI), allows the decision maker give, for each indicator, a desired number of reference levels to assess the goodness of its possible values. Then, its combination with the well-known DEA method is carried out, by comparing the performance of each university (compensatory and non-compensatory) with their resources. Within the scopes of multicriteria and higher education field, the results obtained are particularly useful because they serve not only to measure the relative position of each university, but also to offer a warning system to assist in strategic decision making
Keywords: Enseñanza superior - Tesis doctorales; Composite indicators; Compensation; Reference point method; Multicriteria Analysis; Higher Education System